2014
DOI: 10.1016/j.jcmg.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Definitions for Moderate-Severe Ischemia in Stress Nuclear, Echocardiography, and Magnetic Resonance Imaging

Abstract: The lack of standardized reporting of the magnitude of ischemia on noninvasive imaging contributes to variability in translating the severity of ischemia across stress imaging modalities. We identified the risk of coronary artery disease (CAD) death or myocardial infarction (MI) associated with ≥10% ischemic myocardium on stress nuclear imaging as the risk threshold for stress echocardiography and cardiac magnetic resonance. A narrative review revealed that ≥10% ischemic myocardium on stress nuclear imaging wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 65 publications
2
131
0
3
Order By: Relevance
“…The clinical meaning of the prognostic stratification is based not only on statistical but also on biological plausibility 14. From the pathophysiological viewpoint, it is consistent with our current knowledge of ischemic heart disease that SE positivity mirrors the functional impact of underlying CAD, which is the strongest predictor of future cardiovascular events 15. With longer follow‐up times of expanding cohorts becoming available, now additional, more refined analyses also can be made.…”
supporting
confidence: 66%
“…The clinical meaning of the prognostic stratification is based not only on statistical but also on biological plausibility 14. From the pathophysiological viewpoint, it is consistent with our current knowledge of ischemic heart disease that SE positivity mirrors the functional impact of underlying CAD, which is the strongest predictor of future cardiovascular events 15. With longer follow‐up times of expanding cohorts becoming available, now additional, more refined analyses also can be made.…”
supporting
confidence: 66%
“…Hence, the presented approach of quantification may underestimate the real extent of ischemia in comparison to nuclear perfusion techniques due to incomplete coverage of the left ventricle. With regard to this problem, Shaw et al [5] recently suggested an approach to overcome the difficulty of modality specific thresholds. They defined high risk CAD patients as those with a probability of having an adverse event being about 5% per year [5].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Consequently, a majority of available studies treat ischemia and necrosis as categorical variables without taking into account, extent or severity. It has been suggested that this additional information may serve as an important factor for correct risk stratification in CAD [5,21]. The objective of the present study was to elaborate a CMR algorithm for the quantification of ischemia and necrosis based on standard first-pass perfusion imaging and to establish it's implications on risk prediction improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Comparison of two sets of images performed at two different time intervals is inherently complicated by the fact that the changes in myocardial perfusion or MBF are not only the result of the specific intervention (for example statin therapy) but are also influenced by biological variability and by the precision and accuracy of the method used. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Visual methods might be accurate but not reproducible, and automated methods might be reproducible but not precise. 20,21 A common practice is to compare patient data to a normal database, but alternative methods are available that compare the two sets of images to each other directly rather than comparing each to a normal database.…”
mentioning
confidence: 99%